Illness perception in patients with Alopecia areata under topical immunotherapy. Issue 2 (11th December 2021) - Nasimi, Maryam; Abedini, Robabeh; Ghandi, Narges; Manuchehr, Fatememasume; Kazemzadeh Houjaghan, Amirmasoud; Shakoei, Safoura
Abstract: Alopecia areata (AA) is a chronic autoimmune‐mediated disorder. There is little research on how AA patients conceptualize their disease. The purpose of this study was to investigate the perception and attitude of patients with AA about their illness. The cross‐sectional study was performed on 102 patients with AA referred to our alopecia clinic. Patients between 16 and 60 years were enrolled in the study. A questionnaire including demographic and clinical characteristics and Illness Perception Questionnaire‐Revised (IPQ‐R) was administered to each patient. More than half of patients (55%) experienced their illness as a long‐lasting (17.3 ± 5.5, median reference score = 18), and timely variable (13.4 ± 2.8, median reference score = 12) disorder. Patients perceived that their illness negatively affects their lives (18.9 ± 4.8, median reference score = 18) and are considered an effective role for themselves in controlling disease (20.3 ± 4.9, median reference score = 18). Moreover, patients had a fairly good accepting of their illness (13.4 ± 2.8, median reference score = 15). We observed significant negative effects of illness on the patient's emotions (21.5 ± 5.5, median reference score = 18). We also found that men had a stronger belief in personal control compared with women (21.5 ± 4.8 vs 19.5 ± 4.8; P = .03). A positive correlation was observed between educational status and illness coherence ( r = .21; P = .03). Most patients with AA considered undesirable consequences of their illness. High scores of negative affective symptoms indicate the harmful effects of this disease on patients' lives leading to problems of mental health.